Impact of Climate Change on Animal Husbandry: A Gender Perspective Study in Meghalaya - Singh, Ram; Feroze, S.M. (Indian Journal of Extension Education, 2020)
The impact of climate change on livestock is a matter of serious concern in the state of Meghalaya. Unprecedented drought like situations in the state of Meghalaya has adversely affected the livestock based livelihood of the livestock farmers. The paper demonstrates the impact on livelihood of animal husbandry of South and West Garo Hills of Meghalaya. Extreme climate variability (ECV) affects both the gender but with different consequences according to their roles and responsibilities. Both men and women were of same opinion that there was a change in weather during last 20 years but the response slightly differed between men and women. Overall more than 80 per cent of households reported diseases and mortality in livestock due to drought. The role of wives increases in decision making on selling of livestock during stress period. The time spent on fodder collection also increased during stress period comparative to normal period due to less access of fodder. New livestock breeds, livestock management and land management technique were the mitigating strategies. The study suggest to initiate the new livestock management techniques and high yielding breeds of small and big animal to uplift the livelihood of the people of the study area.
Keywords: Change; Climate; Gender; Husbandry; Impact; NEHR